Using Ogden table approach in mobile applications to personal injury claim / Hussin Abdul Hamid - Abdul Hamid, Hussin (2019)
Personal injury claim can be found if any accident occurs such as road accident. After the accident occur the victim which is humankind can claim the compensation to himself regarding to injury in that accident. This claim involve law to determine the compensation amount to the victim. Unfortunately, in Malaysia multiplier-multiplicand approach still used by the court. This approach are outdated and unfair to victim as it's not see through the victim personal condition. So, this study is to introduce the personal injury claim application which is it using Ogden table to calculate the compensation amount to victim. This Ogden table is special since it's see through in all aspect of victim personal condition. This application are build using Android Studio and Atom. This application have information about claimant, court and lawyer. It also can calculate the compensation amount more accurately to claimant. The target users of this application is claimant which is the victim, lawyer and court.